2020
DOI: 10.31349/suplrevmexfis.1.3.49
|View full text |Cite
|
Sign up to set email alerts
|

Optical biosensor for biogenic amines detection used a porous silicon matrix

Abstract: The content of biogenic amines has been studied due to the toxicity of these compounds in humans when are consumed exogenously, and is used as an indicator of quality in the food industry. The manly method for its determination is high performance liquid chromatography. However, it requires a long time for analysis. An alternative method is the use of biosensors, porous silicon with gold nanoparticles were obtained by electrochemical attack assisted with metal salt. These substrates were used for the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In Figure 4a, topography of a-Si biosensor surface is observed, in which changes in the integrity of the platform are seen, these modifications could be generated by the oxidative activity from piranha solution (activation process); where, in the higher areas, amorphous silicon thin film is observed without modifications, while in the deeper areas the platform oxidation is revealed. Meanwhile, in Figures 4b and 4c, glutaraldehyde polymers generated during functionalization step are enclosed with a white circle, and whose structure is similar to the one reported by Guibal et al (2014) and Contreras et al (2020). Although, the antibodies bound to the surface cannot be observed with the SEM technique, Naja et al (2007) reported that after the binding of antibodies to gold nanoparticles and the subsequent analysis by SEM, villi-like structures were observed and these were not previous binding of antibodies to the nanoparticles; in Figure 4, structures can be like the ones reported by them.…”
Section: Detection Of Salmonella Typhimurium In Natural Orange Juice Samples Using A-si Biosensorssupporting
confidence: 59%
“…In Figure 4a, topography of a-Si biosensor surface is observed, in which changes in the integrity of the platform are seen, these modifications could be generated by the oxidative activity from piranha solution (activation process); where, in the higher areas, amorphous silicon thin film is observed without modifications, while in the deeper areas the platform oxidation is revealed. Meanwhile, in Figures 4b and 4c, glutaraldehyde polymers generated during functionalization step are enclosed with a white circle, and whose structure is similar to the one reported by Guibal et al (2014) and Contreras et al (2020). Although, the antibodies bound to the surface cannot be observed with the SEM technique, Naja et al (2007) reported that after the binding of antibodies to gold nanoparticles and the subsequent analysis by SEM, villi-like structures were observed and these were not previous binding of antibodies to the nanoparticles; in Figure 4, structures can be like the ones reported by them.…”
Section: Detection Of Salmonella Typhimurium In Natural Orange Juice Samples Using A-si Biosensorssupporting
confidence: 59%